A scoping review of design requirements for a home-based upper limb rehabilitation robot for stroke. Issue 6 (18th August 2022) - Li, Lutong; Fu, Qiang; Tyson, Sarah; Preston, Nick; Weightman, Andrew
ABSTRACT: Background: Home-based robotic therapy is a trend of post-stroke upper limb rehabilitation. Although home-based upper limb rehabilitation robots have been developed over several decades, no design specification has been published. Objectives: To identify and synthesize design requirements considering user and technology needs for a home-based upper limb rehabilitation robot through a scoping review. Method: Studies published between 1 January 2000 and 10 June 2020 in Scopus, Web of Science and PubMed database regarding design requirements for upper limb rehabilitation robots from of stroke survivors or therapists were identified and analyzed. We use 'requirement' as something that is needed or wanted. Two physiotherapists ranked the requirements identified from literature review. Results: Nine studies were selected for review. They identified 42 requirements regarding functionality (n = 11, 26.2% of total requirements), usability (n = 16, 38.0% of total requirements), software (n = 14, 33.3% of total requirements) and safety (n = 1, 2.4% of total requirements). The main implementation barriers with respect to adherence and monitoring were space, operation, and cost. Conclusion: This is the first research to summarize the design requirements for home-based upper limb rehabilitation robots for stroke survivors. The need for a safe, comfortable, easy to use device which can be individualized and promote specific movements and tasks emerged. The result of this paper captures the design requirements that can be used in future for the development of a design specification. It provides designers and researchers guidance about the real-world needs for home-based upper limb rehabilitation robots for stroke.